A comparison of the changes in serum lactate between surgical repair and transthoracic device closure of ventricular septal defects in pediatric patients - Huang, Jiang-Shan; Chen, Yu-Kun; Lin, Shi-Hao; Chen, Qiang; Cao, Hua; Zheng, Yi-Rong (Frontiers in Cardiovascular Medicine, 2023)
Objective: The purpose of this study was to compare the changes in serum lactate between surgical repair and transthoracic device closure of ventricular septal defects (VSDs) in pediatric patients. Methods: This study was a retrospective analysis, and 314 pediatric patients with simple VSD from October 2019 to October 2021 were selected. The patients were divided into the S group (surgical repair) and the D group (transthoracic device closure). The serum lactate value at ICU admission and 6 h after operation and the maximum serum lactate value were collected, and the 6-h serum lactate clearance rate was calculated. Result: Through propensity score matching, 43 pairs of cases were successfully matched. Compared with the S group, the D group had a shorter operation duration, ventilation duration, and ICU duration and a lower drainage volume and total hospitalization cost. There was no significant difference between the two groups in the initial and maximum serum lactate values after VSD closure, while the 6-h serum lactate value in the D group was significantly lower than that in the S group, and the 6-h serum lactate clearance rate in the D group was 5 times faster than that in the S group. In addition, the 6-h serum lactate clearance rate in the S group was mainly related to the operation time, CPB time, and ventilation time, while the 6-h serum lactate clearance rate in the D group was only related to the operation time. Conclusion: The initial and maximum serum lactate levels were not significantly different between surgical repair and transthoracic device closure of VSD, but the 6 h serum lactate clearance rate of device closure was 5 times faster than that of surgical repair.